Single-Genotype Syntrophy by Rhodopseudomonas palustris Is Not a Strategy to Aid Redox Balance during Anaerobic Degradation of Lignin Monomers - Doud, Devin F. R.; Angenent, Largus T. (Frontiers in Microbiology, 2016)
Rhodopseudomonas palustris has emerged as a model microbe for the anaerobic metabolism of p-coumarate, which is an aromatic compound and a primary component of lignin. However, under anaerobic conditions, R. palustris must actively eliminate excess reducing equivalents through a number of known strategies (e.g., CO2 fixation, H2 evolution) to avoid lethal redox imbalance. Others had hypothesized that to ease the burden of this redox imbalance, a clonal population of R. palustris could functionally differentiate into a pseudo-consortium. Within this pseudo-consortium, one sub-population would perform the aromatic moiety degradation into acetate, while the other sub-population would oxidize acetate, resulting in a single-genotype syntrophy through acetate sharing. Here, the objective was to test this hypothesis by utilizing microbial electrochemistry as a research tool with the extracellular-electron-transferring bacterium Geobacter sulfurreducens as a reporter strain replacing the hypothesized acetate-oxidizing sub-population. We used a 2x4 experimental design with pure cultures of R. palustris in serum bottles and co-cultures of R. palustris and G. sulfurreducens in bioelectrochemical systems. This experimental design included growth medium with and without bicarbonate to induce non-lethal and lethal redox imbalance conditions, respectively, in R. palustris. Finally, the design also included a mutant strain (NifA*) of R. palustris, which constitutively produces H2, to serve both as a positive control for metabolite secretion (H2) to G. sulfurreducens, and as a non-lethal redox control for without bicarbonate conditions. Our results demonstrate that acetate sharing between different sub-populations of R. palustris does not occur while degrading p-coumarate under either non-lethal or lethal redox imbalance conditions. This work highlights the strength of microbial electrochemistry as a tool for studying microbial syntrophy.